The accountants and management ownership :an empirical test on financial reporting quality - Puat Nelson, Sherliza (Kuala LUmpur, 2010)

(untitled)
The objective of the study is to investigate two of the human capital factors, such as basic skills and professional competencies, supported by behavioural and expertise literatures, in the context of financial reporting quality. Thus, to investigate the background of audit committees from three aspects of experts, such as: the accounting affiliated audit committees, audit committees with postgraduate qualification, and audit committee with managerial experience. Since among the human capital components are: basic skills, professional competencies and complex function. The findings both support and extend those of prior literatures, where leverage and management ownership are significant and related to the financial reporting quality as expected from prior research findings. Most importantly, suggests that accounting affiliated audit committees are associated into improving the quality of financial reporting thus, confirms the important roles of audit committee in monitoring.